1997
DOI: 10.1093/molehr/3.11.953
|View full text |Cite
|
Sign up to set email alerts
|

Modified guanidinium thiocyanate method for human sperm DNA isolation

Abstract: Mammalian sperm chromatin is highly condensed, so isolating DNA from such chromatin can be a formidable task. The procedures that produce high quality DNA from somatic cells fail to yield quality sperm DNA. In this study we have modified the previously used guanidinium method to make it simple and efficient in isolating human sperm DNA. In our method, the lysis buffer contained guanidinium, sodium citrate, sarkosyl, proteinase K and mercaptoethanol. Proteinase K was not used in the original guanidinium method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
9

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 15 publications
1
21
0
9
Order By: Relevance
“…Due to their structure, sperm cells may need a more stringent protocol (longer 98 8C hotstart period) to release DNA [15]. Two semen samples were diluted so that approximately 100 cells were added to the amplification reactions.…”
Section: Str Profiling Directly From Blood and Other Forensically Relmentioning
confidence: 99%
“…Due to their structure, sperm cells may need a more stringent protocol (longer 98 8C hotstart period) to release DNA [15]. Two semen samples were diluted so that approximately 100 cells were added to the amplification reactions.…”
Section: Str Profiling Directly From Blood and Other Forensically Relmentioning
confidence: 99%
“…However, it is clear that the use of the DNeasy Blood & Tissue Kit is limited by its high cost (Bailes et al, 2007), and extraction with phenol-chloroform is a laborious and potentially hazardous method (Sepp et al, 1994), where a significant amount of DNA can be lost (Goldenberger et al, 1995) and degraded (Hossain et al, 1997) and the PCR inhibited (Goldenberger et al, 1995). By contrast, Chelex-100 resin emerged as a cheap, effective, fast, and simple method, which can be realized in few steps, and does not require the use of organic solvents, which confirms observations of previous studies (Walsh et al, 1991;Simonato et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, mammalian tissues exhibit considerable variation in their structures; therefore, one DNA extraction technique might not be suitable for all tissue types (Hossain et al, 1997). Sperm cells present a high degree of nuclear compaction by protamines (Griffin, 2013) and a strong nuclear membrane (Horsman et al, 2005), which inhibits the extraction of sperm DNA by standard techniques used for somatic cells (Hossain et al, 1997;Griffin, 2013), as observed in goat sperm DNA extractions (Silva et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DNA isolation was performed using a protocol that involves two steps: Lysis and extraction. Lysis of spermatozoa was done as per Hossain et al (1997), while the extraction of DNA was done by standard Phenol Chloroform extraction procedure (Sambrook and Russell, 2001). The concentrations of DNA were measured using Biospec-nano-spectrophotometer (Schimadzu Cooperation, Japan).…”
Section: Methodsmentioning
confidence: 99%